THE IMPLEMENTATION OF WRITE, SHARE, AND REVISE TECHNIQUE TO EMPOWER STUDENTS’ CHARACTER DEVELOPMENT AND INTEREST IN WRITING ENGLISH - Inayah, Ratih (English Education Department of STKIP Pasundan, 2019)
This study aims to: (1) examine the influence of Write, Share, and Revise technique in recognizing students‟ interest in writing English; and (2) analyze students' character development in writing skills after applying Write, Share, and Revise. It is a qualitative descriptive research where the primary data analyzed is the development of students‟ writing interest and skill during the time of implementation of Write, Share, and Revise Technique. In addition, as secondary data, the analysis of interviews, and classroom observations were tabulated as supporting primary data. Participants selected by using Purposive Participant technique. A total of 60 regular students of the 2017 English Education Study Program at IKIP Siliwangi were involved. The results of the study showed an increase in students‟ interest in writing English and also help them to develop their own writing skill form before the implementation, during, and after the implementation of Write, Share, and Revise technique. Based on interview and observation, it also reveals that students‟ are still struggle with writing materials. This implies that the students still needed extra care from teachers. Thus, it can be concluded that Write, Share, and Revise technique affects the process of writing as an individual and group. By doing Write, Share, and Revise, students tend to be opening minded and lessen selfish feeling and ego by helping each other to make a better writing form.